Republic of Trinidad and Tobago : Report on the Observance of Standard and Codes - Accounting and Auditing - World Bank (Washington, DC, 2013)
The Report on the Observance of Standard and Codes (ROSC) Accounting and Auditing (A&A) focuses on the institutional framework underpinning national accounting and auditing practices, and their conformity with international standards and good practices. It evaluates the: a) adequacy of reporting requirements, b) capacity to implement applicable standards and codes, and c) the effectiveness of enforcement mechanisms for ensuring compliance with applicable standards and codes. This report provides an assessment of corporate sector accounting, financial reporting, and auditing practices in Trinidad and Tobago. It aims to assist the Government of Trinidad and Tobago's efforts to strengthen accounting and auditing practices and enhance financial transparency in the corporate sector, so as to support the Government's objective of private sector-led growth and deepened integration with the international economy. Trinidad and Tobago is a relatively small, open economy with a high per capita income and abundant natural resources. Key areas for strengthening Trinidad and Tobago's corporate financial reporting practices are: 1) establishing a culture of compliance; 2) improving monitoring and enforcement capabilities of various regulators; 3) establishing institutional mechanisms for regulating the accounting profession, including independent oversight; 4) enhancing technical capacities of Institute of Chartered Accountants of Trinidad and Tobago (ICATT); 5) improving professional accountancy education and training; and 6) improving the statutory framework for corporate financial reporting. The recommendations in this report are presented for the consideration of authorities in Trinidad and Tobago as suggested inputs for the development of a country action plan, geared toward strengthening the corporate financial reporting regime.